Teachers’ Perceptions of Inadequate Outdoor Play Among Preschool Children in Aba, Abia State, Nigeria - Emmanuel Lucas Nwachukwu; Nwamaka Goodness Egbue; Ijeoma VictorNwakaku; Unegbu Lasbrey Ikechukwu (Asian Journal of Early Childhood and Elementary Education, 2026)
Although outdoor play is widely recognized as essential to early childhood development, its provision in many preschool settings remains inadequate. This study examined preschool teachers’ perceptions of inadequate outdoor play provision in Aba, Abia State, Nigeria, with particular attention to its availability, developmental implications, and implementation constraints. A descriptive survey design was employed involving teachers in registered public and private preschools. Using multistage sampling based on Yamane’s formula with a 5% margin of error, 212 questionnaires were distributed, and 200 valid responses were analyzed. Data were analyzed using descriptive statistics and chi-square tests. The findings indicate that outdoor play provision remains inadequate, as reflected in limited space, restricted daily access, insufficient time allocation, and safety concerns (cluster mean = 2.26). Teachers also agreed that limited outdoor play adversely affects children’s physical activity, peer interaction, classroom behaviour, and attention regulation (cluster mean = 3.47). No significant subgroup differences were identified. These findings reveal a persistent gap between teachers’ recognition of the developmental importance of outdoor play and the structural conditions constraining its implementation. The study concludes that improving outdoor play provision requires stronger facility standards and greater reinforcement of play-based pedagogy in early childhood education settings.